A IOT Frame work for Accident Detection, Vehicle Monitoring and Accident Alert - Arpitha Martin; Vani Sapthasagar, (International Journal of Management Studies (IJMS), 2019)
Road accidents rates are very high nowadays, especially two wheelers. Timely medical aid can help in saving lives. This system aims to alert the nearby medical centre about the accident to provide immediate medical aid. The attached accelerometer in the vehicle senses the tilt of the vehicle and the heartbeat sensor on the user’s body senses the abnormality of the heartbeat to understand the seriousness of the accident. Thus, the systems will make the decision and sends the information to the cloud, connected via Wi-Fi module (ESP-01) and accelerometer and heartbeat sensor. The system will send text message to the nearest medical centre and friend by sharing the exact location of the accident that can save the time to assist the victim. Initially, the GPS continuously takes input data from the satellite and stores the latitude and longitude values in AT89s52 microcontroller's buffer. If we need to track the vehicle, we have to send a message to GSM device, by which it gets activated. It also gets activated by detecting accident on the shock sensor connected to vehicle. Parallelly, deactivates GPS with the help of relay. Once GSM gets activated it takes the last received latitude and longitude positions values from the buffer and sends a message to the particular number and information is stored in cloud which is predefined in the program. Once message has been sent to the predefined device the GSM gets deactivated and GPS gets activated.